Analyzing the Role of Money Balances as a factor of Output in Context of Globalization: A Case Study of Bahrain - Elayah, Wahib Ali Musleh; Hu, Wen; Mohammed, Othman; Haq, Ihtisham ul; Awais, Muhammad (iRASD Journal of Economics, 2021)
The nexus between money and output is regaining attention from researchers after recent global financial crisis. Likewise, globalization-output nexus also grabs the attention of researchers. Henceforth, the study is design to analyze the effect of real money balances and globalization on output by incorporating real money balances and globalization in Cobb-Douglas production function. Time series data has been analyzed and all variables of the study are tested for order of integration through unit root test. So, it is found that that all variables are integrated of first order so one cannot apply ordinary least squares. This is the reason that Johansen cointegration technique and the cointegration regression, fully modified least squares, are applied for long run relationship and long run estimates respectively. The cointegration technique confirmed long run relationship among variables thus; it is concluded that real money balances and globalization are important determinants of output in the Kingdom of Bahrain. Furthermore, results of the study show that real money balances and globalization are found to have positive and significant effect on output along with labor and capital. Thus, this study concludes that real money balances and globalization are important factors of output in the Kingdom of Bahrain and monetary authorities should consider real money balances and globalization in policy making for sustainable economic growth.